Development of Boccia Balls in Children with Special Needs and Physically Impaired - Arizky Ramadhan; Iyakrus; Hartati; Wahyu Indra Bayu; Herri yusfi; Yahya Eko Nopiyanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
The purpose of this study was to determine the results of the development of boccia balls to find valid and effective children with special needs disabilities at SLB-D.D1 YPAC Palembang City. The study is a research and development (R&D) research and development with the stages of borg & gall. The subjects of the study were students of SLB D.D1 YPAC Palembang City, 10 people on a small scale and 20 people on a large scale. Data were collected through questionnaires and skills tests. Data analysis used percentage analysis and paired sample t-test. The results of the final product of this study are in the form of boccia ball media which are intended for training children with special needs at SLB D.D1 YPAC Palembang City in practicing and playing boccia games. The development product has a very feasible meaning through the validation value of the media expert, which is 100% and the game expert, which is 91.67% very valid with an average validation value of 95.8% very valid. The effectiveness test explains that the developed boccia ball has an effect on improving the boccia game skills of special needs children at SLB D.D1 YPAC Palembang City, which is marked by a change in skills of 24.2 from the previous 17.1 in the early test and 25.4 from the previous 16.8 in the field test. The usefulness of this product is able to improve the achievements of boccia athletes in Palembang City. Helping coaches overcome the shortcomings of the training facilities aspect, namely the very minimal ball equipment and helping to accelerate the development of Boccia sports achievements in Palembang. The novelty of this research is developing media and facilities for matches and training in the form of balls, meeting the expected achievement of match results, getting used to adapting to balls that have standard weight and meeting the lack of ball media for training.